Statistical process control in agribusiness company - Franken, Diogo Ariel; Hammes, Juliano; Polacinski, Édio; Lorenzett, Daniel Benitti; Godoy, Leoni Pentiado; Godoy, Taís Pentiado (Revista de Administração da UFSM, 2014)
This article aims to present an application of statistical process control (CEP) in an agribusiness company, located in the state of Rio Grande do Sul, which is an international benchmark in its segment. Therefore, we performed a case study, using the documentary research and semi-structured interviews to collect data. More specifically, initially determined through a theoretical study, the main approaches concerning the proposed theme, which were the statistical quality control (CEQ), CEP, control charts, histograms, potential capacity of the process (CP) and actual capacity of the process (CPK), and then present based on documentary research and semi-structured interviews, the application of CEP considered. How majors search results, it is noteworthy that it was possible to present the proposed application for the item AH225962 considered, allowing to understand the importance of a correct application of the CEP tool, to ensure quality of products, the agribusiness company considered. It is expected that the learning from this study contribute in the dissemination of experiences and practices of using CEP from real situations, companies that are a benchmark in its segment.